Cultivo consorciado de lagostas (Panulirus meripurpuratus) em uma maricultura multitrófica em Guarapari ES - Souza, Marcelo Lacerda Teixeira de (2021)
Mariculture is a specific branch of aquaculture that encompasses the production of a wide variety of marine and estuarine aquatic organisms, such as fish, mollusks and crustaceans. Among the latter, there is an obstacle to the development of mariculture techniques in the production of lobster species, mainly due to the long duration of the larval stages of these organisms. Lobsters of the genus Panulirus have the longest and most complex development among decapod crustaceans, taking up to two years to metamorphose into puerulus, making the production of these organisms in captivity complex. One of the possibilities to make the production of this species viable is through consortiated rearing. The objective of this study was to evaluate the viability of the cultivation of lobsters (Panulirus meripurpuratus), acquired through passive capture in the cultivation structures of a marine farm, on different consortiums with oysters, scallops and under a fish tank, checking its growth over a period of 6 months. To enable the verification of growth rates in each organism, the young forms of P. meripurpuratus were individually marked with a Visible Implant fluorescent elastomer system (VIE). The results showed that there were no significant differences between treatments, with a constant growth of organisms in the different treatments throughout the experiment. Total length values in the different treatments ranged from 2.9 ± 0.4 cm to 6.3 ± 0.8 cm in the TANQUE (Tank) treatment, from 2.5 ± 0.6 cm to 5.3 ± 0.6 cm in the VIEIRA (Scallop) treatment and from 2.9 ± 1.1 cm to 5.8 ± 1.1 cm in the OSTRA (Oyster) treatment. Survival rates were 60% for the TANK treatment, 45% for the VIEIRA treatment and 50% for the OSTRA treatment. 55 seedlings were registered for the TANQUE and VIEIRA treatment and 59 seedlings for the OSTRA treatment. The retention of VIE tags was 95.1%, demonstrating the high efficiency of this tagging technique. The present study showed that young forms of lobsters of the species P. meripurpuratus have a high tolerance to different cultivation methods, are resistant to handling, storage and food availability. Thus, it is concluded that increasing the production of the marine farm with the fattening of lobsters without increasing costs is technically feasible, considering a diet with organisms already available in the community associated with the cultivation structures.